Perceived stress, social support and social media addiction in university students during covid-19 pandemic - Taş, Filiz (Journal of Dependence, 2022)
Objective: The purpose of the study is to examine the relationship between perceived stress, perceived social support and social media addiction in university students.Method: The research is a descriptive, relational study. The sample consisted of 404 students studying at the Faculty of Health Sciences. Personal Information Form, Perceived Stress Scale, Perceived Social Support Scale, and Social Media Addiction Scale-Adult Form were used for data.Results: During the pandemic period, 71.8% of students used their mobile phones for study. 73.8% stated that their study hours have decreased. 94.1% of the students stated that the time spent at home increased, and 91.8% stated that there was an increase in the hours of using a computer or phone due to the pandemic. There were significant differences between perceived stress, social support, and social media addiction levels according to various demographic variables.Conclusion: The results showed that 86.9% of students increased their time spent online during the pandemic period. It was concluded that perceived stress and social support affect social media addiction.
Keywords: COVID-19; students; stress; social support; social media addiction